Clinical outcomes and costs : a comparison between spinal anaesthesia and intra-venous general anaesthesia for emergency caesarean sections at a regional hospital in Swaziland - Rheeder, Paul (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.